Dinimishing Musharakah Contract as an Alternative Financing for Small and Medium-Sized Enterprises - Imronudin, I (Universitas Muhammadiyah Surakarta, 2015)
Given the fact that the utilization of Islamic financial contract based on the PLS principle is relatively low, it is important to propose new insight of using Islamic financial instrument under PLS principles. Therefore, this paper aims to provide insight of using diminishing musharaka contract as an alternative financing for Small and Medium-sized Enterprises (SMEs), which operate under PLS principles. Descriptive analytical method is used to describe the use of diminishing musharaka contract. Using simple calculation, this paper shows how to apply this type of contract to finance investment for SMEs particularly in fixed assets. Based on the diminishing musharaka contract, the profit which is shared to Islamic banks decrease gradually in response to the amount of decreasing banks’ capital involve in partnership. Conversely, the proportion of profit for SMEs increases gradually as a consequence of the increasing amount of partnership with Islamic banks. Thus, diminishing Musharaka contract enables SMEs to release the contract without undergoing financial distress because they make repayment of the principle in installment together with the profit sharing.